First identification of potato tuber rot caused by Penicillium solitum, its silver nanoparticles synthesis, characterization and use against harmful pathogens - Shah, Syed Haseeb; Shan, Xiaoliang; Baig, Sofia; Zhao, Hongwei; Ismail, Bushra; Shahzadi, Irum; Majeed, Zahid; Nawazish, Shamyla; Siddique, Maria; Baig, Ayesha (Frontiers in Plant Science, 2023)
Potato is one of the highly consumed vegetable crop grown in different regions across Pakistan that is affected by fungal diseases. The current research was conducted to identify fungal pathogen causing mold-like disease of potato in Khyber Pakhtunkhwa (KP), Pakistan. For molecular identification and characterization of fungal disease; potato tuber samples were collected followed by culturing on potato dextrose agar (PDA). Based on morphological features, the pathogen was identified as a Penicillium species. This result was obtained in 45 different isolates from potato tubers. Molecular identification was done using β-tubulin primers and ITS5 sequencing of 13 different isolates that releveled 98% homology with BLAST (GenBank accession no. KX958076) as Penicillium solitum (GenBank accession nos. ON307317; ON307475 and ON310801).Phylogenetic tree was constructed that showed Penicillium solitum prevalence along with Penicillium polonicum and Penicillium citrinum on potato tubers. Based on this, Penicillium solitum based silver nanoparticles (Ag NPs) were synthesized and characterized using UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), energy dispersive X-ray (EDX) and field emission scanning electron microscopy (FE SEM). UV-analysis showed a characteristic peak at 410 nm confirming synthesis of Penicillium solitum based Ag NPs. This was further confirmed by XRD followed by EDX and SEM that showed face cubic crystal structure with Ag as major constituent of 18 nm formed spherical Ag NPs. FTIR showed band stretching of O-H, N-O and C-H of biological origin. Similarly, Penicillium solitum based Ag NPs presented strong anti-bacterial and anti-fungal activity at 0.5 level of significance LSD. According to our knowledge, this is the first report of Penicillium solitum identification in Pakistan, its Ag NPs synthesis and characterization to be used against pathogens of agricultural significance.